Comedy at its “Prime:” Comic Elements in Muriel Spark’s The Prime of Miss Jean Brodie - Ancheta, Maria Rhodora (Journal of English Studies and Comparative Literature; Vol 9 No 1 (2006), 2007)
Excerpt Muriel Spark has been alternately called “ the reasonable recorder of unreason” (Barreca 223), and “the surrealist Jane Austen” (126) by Charles Alva Hoyt. Hoyt goes on to call her “ a thoroughly mischievous writer…view[ing] the universe itself as mischievous…both aware of individuals and fond of meddling with them for its own amusement” (126). From thence proceed her comic impulses, as seen in her works. I am, in this paper, commencing by agreeing with Hoyt, but am also going beyond this universalized, “classical-ized” explication by specifying this “unreason” to be more than a cosmological phenomenon in Spark’s fiction. Citing Hoyt, perhaps the operative word we should be focusing on here is surrealist rather than the “Jane Austen-ish” qualities that Spark is purported to carry in her texts. At least, in The Prime of Miss Jean Brodie (1961), I find the Romantic a very comfortable and convenient veneer overlaying what is actually a hard-nosed, almost cynical attempt to deal with the multiple vacuums within the matrix of the “Brodie world”. Hoyt himself debunks this comparison when he says that although she is not a Romantic, Mrs. Spark is perfectly willing, like every other modern writer to accept some of the advantages secured by Romanticism, principally those implied in the postulate that individual experimentation is equal or superior to [the] observation of the most correct models. (128, my italics)